(untitled) (TEST Ticontre. Theory Text Translation, 2014)
I quattro componimenti che qui si presentano appartengono alla prima opera poetica di Claudio Rodríguez (Zamora 1934 – Madrid 1999) che può essere certamente considerato uno dei maggiori poeti della seconda metà del Novecento spagnolo, e che le storie letterarie convenzionalmente ascrivono alla cosiddetta “Generación de los Cincuenta”, un consistente gruppo di autori di altissimo valore letterario, ancora poco conosciuti in Italia. L’opera lirica di Rodríguez comprende cinque raccolte: Don de la ebriedad (1953), Conjuros (1958), Alianza y Condena (1965), El vuelo de la celebración (1976) e Casi una leyenda (1991). Esile quanto intensa attività, che gli valse una ventina di importanti premi letterari e l’elezione a membro “de número” della Real Academia Española (1987). The four poems hereby analysed are included in the first edited collection by Claudio Rodríguez (Zamora 1934 – Madrid 1999), one of the most representative authors belonging to the generation of Spanish poets of the second half of the 20th century. A group of poets of the highest literary value conventionally defined by literary critics as “Generación de los Cincuenta”, still hardly known in Italy. Rodríguez published five collections of lyrical poems: Don de la ebriedad (1953), Conjuros (1958), Alianza y Condena (1965), El vuelo de la celebración (1976) and Casi una leyenda (1991). His modest but intense literary production earned him a score of prestigious literary awards, as well as the election as member of the Real Academia Española (1987).